Comprehensive Textbook Of Echocardiography - Nanda, Navin C. (New Delhi : Jaypee Brothers Medical Publishers, 2014)
Practical guide to echocardiography for trainees. Covers history and basics and how to perform different types of echocardiograph for various heart disease groups
Guía práctica de ecocardiografía para aprendices. Cubre la historia y los conceptos básicos y cómo realizar diferentes tipos de ecocardiografía para varios grupos de enfermedades cardíacas
Volumen 1 Section 1 : History an d basic Section 2: Echocardiography/ultrasound examination and training Section 3. Valvular heart disease
Keywords: : ECOCARDIOGRAFÍA; CARDIOPATÍAS CONGÉNITAS; ENFERMEDAD CORONARIA